A Regional Competitive Framework for Indonesian Sectoral Strategy: Enhancing Plantation Potency in West Papua - Khusniati, Navi'ah; Wuri, Margaretha Arnita (Jurnal Dinamika Sosial Ekonomi, 2025)
This study examines the structure and dynamics of the regional economy of West Papua Province by identifying base and non-base sectors using the Location Quotient (LQ) and Shift Share approaches. The analysis is based on district- and city-level Gross Regional Domestic Product (GRDP) data at constant prices for the period 2012–2022. The LQ estimates indicate that the agricultural sector particularly the plantation subsector exhibits a strong comparative advantage, with 10 out of 13 administrative regions recording LQ values greater than one. The Shift Share analysis reveals substantial heterogeneity in regional competitiveness. Fak-Fak, Kaimana, Manokwari, and Teluk Wondama are classified in Quadrant I, indicating that the plantation subsector in these regions functions not only as a base sector but also demonstrates relatively faster growth compared to the provincial average. In contrast, South Manokwari, Maybrat, Raja Ampat, South Sorong, Tambrauw, and Pegunungan Arfak fall into Quadrant IV, suggesting base sectors with relatively lagging growth performance. Based on these findings, this study emphasizes the development of the coconut industry as a strategic driver of a renewable natural resource–based economy. Nevertheless, the sector continues to face major constraints, including low productivity, high post-harvest losses, and limited market access. Therefore, policies aimed at strengthening value chains, adopting green technologies, and advancing digital governance are essential prerequisites for enhancing regional competitiveness and ensuring the long-term economic sustainability of West Papua.